Adoption of crop insurance and impact: insights from India - Aditya K S; Md Tajuddin Khan; Avinash Kishore (Agricultural Economics Research Review, 2023)
Agriculture is inherently a risky enterprise because of its dependence on rainfall. To mitigate risks, farmers diversify crops and enterprises, maintain stabilization account or resort to the sale of assets. Crop insurance is a complementary institutional mechanism that aids farmers to cope with risks better. Considering the importance of crop insurance in risk mitigation, this paper using data from a large-scale farmers’ survey we identify the factors that influence farmers’ decision to buy crop insurance and subsequently assess its impact on farm income, production expenses and productive investments in agriculture. Farmers’ adoption of crop insurance is low— 4.80% kharif season and 3.17% in the rabi season mainly on account of lack of awareness about insurance products. Nevertheless, the probability of adoption of insurance is higher for those who experience higher crop loss and have some formal training in agriculture. The subsidy on premium also positively influences crop insurance uptake decisions. On the other hand, the factors like the lower social status, tenant farming and exposure to deficit-rainfall in the previous year are negatively associated with the decision to insure. The results on the impact of insurance are not conclusive to prove that insured farmer subsumes higher risks compared to the uninsured.